2022
DOI: 10.1002/suco.202100551
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of RC columns strengthened with UHPFRC jackets through grooving method under eccentric loading: A comparative evaluation of steel and synthetic macro fibers in UHPFRC

Abstract: This study aims to examine the behavior of reinforced concrete (RC) circular columns retrofitted with ultra‐high‐performance fiber‐reinforced concrete (UHPFRC) jackets and fiber‐reinforced polymer (FRP) wraps under concentric and eccentric loading. In the present study, for the first time, UHPFRC jackets containing synthetic macro fibers (barchip) were used. The results were then compared with those obtained by UHPFRC containing steel fibers. Moreover, to improve the effect of concrete jacketing on the column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…[9][10][11] Existing steel reinforced HSC columns (SRHSC columns) may need strengthening or retrofitting due to material deterioration under extreme environmental conditions, an increase in the applied load (i.e., emerging heavier trucks in transportation structures) and the change in the functions of the structures. [12][13][14] Fiber-Reinforced-Polymer (FRP) has been considered an ideal strengthening material for improving the deformation and load carrying capacity (LCC) of HSC columns due to its advantages of being free from corrosion with high fatigue resistance and stiffness, high strength-to-weight ratio, less maintenance and fast and easy installation. [15][16][17][18][19] Due to the great potential of FRP for strengthening HSC columns, a significant number of investigations have been devoted to FRP strengthened HSC columns and HSC filled FRP tube (fiber oriented in transverse direction only) in order to capture the stress-strain response and performance of HSC columns with FRP strengthening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Existing steel reinforced HSC columns (SRHSC columns) may need strengthening or retrofitting due to material deterioration under extreme environmental conditions, an increase in the applied load (i.e., emerging heavier trucks in transportation structures) and the change in the functions of the structures. [12][13][14] Fiber-Reinforced-Polymer (FRP) has been considered an ideal strengthening material for improving the deformation and load carrying capacity (LCC) of HSC columns due to its advantages of being free from corrosion with high fatigue resistance and stiffness, high strength-to-weight ratio, less maintenance and fast and easy installation. [15][16][17][18][19] Due to the great potential of FRP for strengthening HSC columns, a significant number of investigations have been devoted to FRP strengthened HSC columns and HSC filled FRP tube (fiber oriented in transverse direction only) in order to capture the stress-strain response and performance of HSC columns with FRP strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…Existing steel reinforced HSC columns (SRHSC columns) may need strengthening or retrofitting due to material deterioration under extreme environmental conditions, an increase in the applied load (i.e., emerging heavier trucks in transportation structures) and the change in the functions of the structures 12–14 . Fiber‐Reinforced‐Polymer (FRP) has been considered an ideal strengthening material for improving the deformation and load carrying capacity (LCC) of HSC columns due to its advantages of being free from corrosion with high fatigue resistance and stiffness, high strength‐to‐weight ratio, less maintenance and fast and easy installation 15–19 …”
Section: Introductionmentioning
confidence: 99%
“…Mastali and Dalvand 9 studied the impact resistance, and mechanical behavior of fiber reinforced compacting concrete modified with NS and silica fume. The impact resistance is regarded as one of the critical concrete properties for applications in civil engineering Zhang et al 10 Numerous studies revealed that randomly dispersed steel fibers (SFs) could remarkably improve the concrete mechanical properties, toughness, impact resistance, post crack behavior, and fatigue properties 11–16 . For instance, Zhao et al 17 studied the combined effect of steel slag and hooked‐end SFs on the fresh and mechanical properties of self‐compacting concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The impact resistance is regarded as one of the critical concrete properties for applications in civil engineering Zhang et al 10 Numerous studies revealed that randomly dispersed steel fibers (SFs) could remarkably improve the concrete mechanical properties, toughness, impact resistance, post crack behavior, and fatigue properties. [11][12][13][14][15][16] For instance, Zhao et al 17 studied the combined effect of steel slag and hooked-end SFs on the fresh and mechanical properties of self-compacting concrete. Matalkah et al 18 investigate the effect of fiber type and dosage on the mechanical and shrinkage properties of alkali-activated kaolin binder.…”
Section: Introductionmentioning
confidence: 99%
“…RESULTS AND DISCUSSION4.1 | Failure patternsGenerally, based on results of many experiments[58][59][60][61][62] related RC columns, the failure modes of the columns are well understand. Figure5illustrated failure patterns of the tested columns.…”
mentioning
confidence: 99%